2022
DOI: 10.1039/d2nj02551e
|View full text |Cite
|
Sign up to set email alerts
|

N, P co-doping triggered phase transition of MoS2 with enlarged interlayer spacing for efficient hydrogen evolution

Abstract: Molybdenum disulfide (MoS2)-based transition-metal chalcogenides are considered to be cost-efficient, environmentally-friendly, and stable materials in the application of electrocatalytic hydrogen production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…23 Feng et al introduced N and P co-doping to prepare ultra-stable 1T–2H MoS 2 . 24 However, 1T-MoS 2 in these studies was randomly distributed in the 2H-MoS 2 domains. To achieve a position-controlled distribution of 1T-MoS 2 , Chhowalla et al used electron-beam exposure technology to expose specific positions by locally soaking in butyl lithium to induce phase transformation in the exposed part and realized the position-controlled distribution of the 1T phase in the 2H main phase.…”
Section: Introductionmentioning
confidence: 89%
“…23 Feng et al introduced N and P co-doping to prepare ultra-stable 1T–2H MoS 2 . 24 However, 1T-MoS 2 in these studies was randomly distributed in the 2H-MoS 2 domains. To achieve a position-controlled distribution of 1T-MoS 2 , Chhowalla et al used electron-beam exposure technology to expose specific positions by locally soaking in butyl lithium to induce phase transformation in the exposed part and realized the position-controlled distribution of the 1T phase in the 2H main phase.…”
Section: Introductionmentioning
confidence: 89%
“…203 However, Feng et al found that the N and P dopants could realize the conversion of 2H MoS 2 to 1T MoS 2 and enlarge the interlayer spacing. 191 Therefore, the dual anion dopants help to improve the conductivity of MoS 2 . In addition, DFT calculations found a smaller G H* value of 0.08 eV on N/P-MoS 2 than that of N-MoS 2 (0.73 eV), P-MoS 2 (0.67 eV), and MoS 2 (2.05 eV), suggesting enhanced HER intrinsic activity.…”
Section: Anion-anion Dual-doped Metal Chalcogenides Pnictides and Othersmentioning
confidence: 99%
“…However, Feng et al. found that the N and P dopants could realize the conversion of 2H MoS 2 to 1T MoS 2 and enlarge the interlayer spacing 191 . Therefore, the dual anion dopants help to improve the conductivity of MoS 2 .…”
Section: Anion–anion Dual‐doped Metal Catalysts For Water Electrolysismentioning
confidence: 99%